A meta-analysis of ferric carboxymaltose versus other intravenous iron preparations for the management of iron deficiency anemia during pregnancy - Sanjay Gupte; Ashis Mukhopadhyay; Manju Puri; P. M. Gopinath; Reena Wani; J. B. Sharma; Onkar C. Swami (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: We conducted a meta-analysis of randomized clinical trials evaluating the clinical effects of ferric carboxymaltose therapy compared to other intravenous iron in improving hemoglobin and serum ferritin in pregnant women. We also assessed the safety of ferric carboxymaltose vs. other intravenous iron. Data source: EMBASE, PubMed, and Web of Science were searched for trials related to ferric carboxymaltose in pregnant women, published between 2005 and 2021. We also reviewed articles from google scholar. The keywords "ferric carboxymaltose," "FCM," "intravenous," "randomized," "pregnancy," "quality of life," and "neonatal outcomes" were used to search the literature. The search was limited to pregnant women. Selection of studies: Studies related to ferric carboxymaltose in pregnancy were scanned. Observational studies, review articles, and case reports were excluded. Randomized studies in pregnant women involving ferric carboxymaltose and other intravenous iron formulations were shortlisted. Of 256 studies, nine randomized control trials were selected. Data collection: Two reviewers independently extracted data from nine selected trials Data synthesis: The final effect size for increase in hemoglobin after treatment was significant for ferric carboxymaltose vs. iron sucrose/iron polymaltose (standard mean difference 0.89g/dl [95% confidence interval 0.27,1.51]). The final effect size for the increase in ferritin after treatment was more for ferric carboxymaltose vs. iron sucrose/iron polymaltose (standard mean difference 22.53µg/L [-7.26, 52.33]). No serious adverse events were reported with ferric carboxymaltose or other intravenous iron. Conclusion: Ferric carboxymaltose demonstrated better efficacy than other intravenous iron in increasing hemoglobin and ferritin levels in treating iron deficiency anemia in pregnant women.